Socio-Cultural Barriers for People with Disabilities in the Public Employment Sector of Nepal - Adhikari, Shukra Raj; Pradhananga, Nisha (GS WOW: Wisdom of Worthy Research Journal, 2024)
Employment is vital for persons with disabilities (PWD) as it fosters financial stability, independence, and purpose. This research investigates the constitutional and legal frameworks affecting PWD's access to public service employment in Nepal, identifying key barriers they encounter. A qualitative research design was employed to analyze relevant constitutional and legal documents. Data collection utilized historical content analysis, case studies, observations, and key informant interviews to uncover barriers faced by employed PWD in accessing public employment.The study involved narratives from ten purposively selected cases of employed individuals with disabilities. Observations focused on the  availability of disability-friendly infrastructure and physical challenges faced by these employees. Key informants included policy advocates and leaders from disability organizations, providing insights into the effectiveness of existing policies. Data analysis was conducted using content analysis methods. Findings indicate that while Nepal's Constitution (2015) and the Act Relating to the Rights of Persons with Disabilities (2017) demonstrate a commitment to enhancing employment opportunities for PWD, significant barriers persist. Public institutions often lack disability-friendly infrastructures, and societal attitudes, coupled with insufficient awareness and training among employers, further  exacerbate discrimination against PWD in public sector jobs. Consequently, individuals with disabilities face exclusion from employment opportunities, limiting their economic participation.